Airport operations management- aplikace na regionální letiště - Jošth Adamová, Eva (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2011)
Záverečná diplomová práca sa zaoberá problematikou Airport Operations Management a jej aplikáciou na regionálne letisko Brno – Tuřany. Rozoberá všeobecné prevádzkové procesy letísk a porovnáva ich so súčasnou situáciou v Tuřanoch. Na základe porovnania sú navrhnuté zlepšenia, alebo návrhy pre zefektívnenie prevádzky. Súčasťou práce je tiež priblíženie súčasnej problematiky ekologizácie letísk a leteckej dopravy.

The main content of this master´s thesis is Airport Operations Management and it´s application on regional airport Brno – Tuřany. The study analyses common airport operations at the airports and compares it with actual situation at Brno airport. Focusing on comparsion, new upgrading or suggestions for increasing the operations are made. The part of thesis encloses also an approach to contemporary issues in greening the airports and air traffic.
Airport operations management - application on regional airport
Keywords: Airport Operations Management; Brno; letisko; prevádzka; ekologizácia; Airport Operations Management; Brno; airport; operations; greening